Management of the complications of pubovaginal sling surgery - Bayrak, Omer; Coskun, Burhan; Dincer, Murat; Onem, Kadir; Onur, Rahmi (The European Research Journal, 2017)
Objective. To present complications of pubovaginal sling surgery (PVS) and their managements.Methods. A total of 21 patients who underwent PVS in 4 different tertiary refferal centers between June 2014 and May 2016 were reviewed retrospectively. Demographic characteristics of the patients, previous 6 history, daily pad use, Urogenital Distress Inventory (UDI-6) and Incontinence Impact Questionnaire (IIQ) were recorded. Also, the management of the complications were stated.Results. The mean age of the patients were 54.9±12.32 (range, 36-76) years. Six (28.5%) patients had a history of previous incontinence surgery and 15 (71.4%) patients were naïve. There were no intraoperative complications. The mean daily pad use was decreased from 4.04±0.95 to 0.95±0.86 (p=0.0001). While mean preoperative UDI-6 scores were decreased from 6.66±2.09 to 2.09±1.22 (p=0.0001) at postoperative sixth month; preoperative mean IIQ-7 scores decreased from 16.8±1.16 to 5.09±4.21 (p=0.0001) at postoperative sixth month. One (4.76%) patient had abdominal hernia at postoperative 2nd year, three (14.28%) patients had an increased post-micturational residual (150-200ml) and two (9.52%) patients had urinary retention. Conclusion. Although the efficiency of PVS is high; one should aware of complications. The successful management of the complications will increase efficiency and patient satisfaction.